تعدد الزوجات عند مسلمي قبيلة يورب : دراسة فقهية مقاصدية - شرف, نجم أديولي
This study aims to investigate issues related to polygamy among Yoruba Muslims and to what extent their practice complies with Shari'ah law and its initial and supplementary purposes (Maqasid). This is to rectify its existing disorders, and to direct and enlighten who wish to practice polygamy in Yorubaland on its benefits for society and the reputation of Islam in the region. This thesis comprises of an introductory chapter and followed by another three chapters. The second chapter aims to shed light on general rules on polygamy and its initial and supplementary purposes (Maqasid). The third chapter discusses the concept of polygamy and how the Yoruba people practice it, their purpose for marrying more than one wife and a comparison between their purposes of practicing polygamy and its legislative objectives. The last chapter examines the challenges facing Muslim polygamous families in Yorubaland through interviews and makes suggestions and recommendations such as the fear of Allah, government intervention, organising educational courses on marriage generally and polygamy specifically, setting up a hesbah (guidance and counselling) for marriage issues and good family management to address those issues. This research uses the inductive and analytical methods to draw information.